Functions Modeling Change: A Preparation for Calculus, 5th Edition

Published by Wiley
ISBN 10: 1118583191
ISBN 13: 978-1-11858-319-7

Chapter 4 - Exponential Functions - Exercises to Skills for Chapter 4 - Page 185: 14



Work Step by Step

Use the fact that $(a^b)^n=a^{bn}$ to rewrite the expression as $$(-1)^{445}=((-1)^2)^{222}(-1)$$ Note that in this example, $2(222)+1=444+1=445$. This expression can be simplified using the fact that $(-1)^2=1$ and that $1^{222}=1$ to get a result of $(1)(-1)=-1$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.